Does strategic ambidexterity moderate organizational support - sales performance relationship for financial services in Uganda? - Musigire, Samuel; Ntayi, Joseph; Ahiauzu, Augustine (African Journal of Business Management, 2017)
Adapting strategic ambidexterity enhances the sales performance of financial services that provide support to their employees, especially the sales representatives. Simultaneously providing support aligned to the needs of existing markets and that which is aligned to needs of new markets attracts potential customers to open accounts and undertake policies in banks and insurance institutions, respectively, and encourages existing account or policy holders to save more with their banks or upgrade their insurance policies. Despite strategic ambidexterity’s important role in the relationship between organizational support and sales performance, existing studies in financial services have concentrated on investigating the direct relationship between these variables. These studies have ignored the role of strategic ambidexterity in moderating the relationship between organizational support and sales performance. This study found that there was a positive and significant impact of strategic ambidexterity in moderating the relationship between organizational support and sales performance of financial services in Uganda.
Keywords: Strategic ambidexterity; organizational support; Sales performance; Financial services